Correlation among Snpb11 markers, root growth, and physiological characters of upland rice under aluminum stress - MIFTAHUL HUDA FENDIYANTO; RIZKY DWI SATRIO; SUHARSONO SUHARSONO; ARIS TJAHJOLEKSONO; M MIFTAHUDIN (Society for Indonesian Biodiversity, 2019)
Abstract. Fendiyanto MH, Satrio RD, Suharsono, Tjahjoleksono A, Miftahudin. 2019. Correlation among Snpb11 markers, root growth, and physiological characters of upland rice under aluminum stress. Biodiversitas 20: 1243-1254. The cultivation of upland rice in acid soils faces aluminum (Al) toxicity. Development of Al-tolerant rice could be one of the solutions to overcome the problem. Marker-assisted breeding to develop Al-tolerant rice requires at least a molecular marker for foreground selection. Snpb11 is a molecular marker developed from the nucleotide differences in a specific allele between Al-tolerant and sensitive rice. Snpb11 has never been used as a molecular marker in rice. Therefore this study aimed to examine the correlation among Snpb11 marker, root growth, and physiological characters under Al stress in upland rice. We used physiological characters and the Snpb11 marker to justify the Al tolerance level in several upland rice varieties. We found that physiological characters, i.e.: primary root length, total root length, chlorophyll, and carotenoid content showed positive correlation to Snpb11. Conversely, root malondialdehyde content, which represents the level of lipid peroxidation showed a negative correlation to Snpb11. There is evidence that the Snpb11 highly correlated with primary and total root length characters, which are the Al tolerance parameters used in rice. Therefore, Snpb11 markers can be used to distinguish the Al tolerance level in upland rice.